Electrochemical Behavior of Graphite Anode in LiF-NaF-KF Eutectic with YF3. (20th January 2017) - Tian, Lifang; Huang, Wei; Jiang, Feng; Zheng, Haiyang; Zhu, Tiejian; She, Changfeng; Wang, Xianbin; Long, Dewu; Gong, Yu; Wu, Guozhong; Li, Qingnuan
Abstract: The electrode reactions and electrolysis process of graphite anode were investigated in LiF-NaF-KF (FLiNaK, 46.5-11.5-42.0 mol%) eutectic with YF3 at 823 K. Two different types of reactions were observed on graphite anode. The graphite was oxidized to carbon mono- and dioxide in a potential range of 0–2 V ( vs. Ni 2+ /Ni, similarly hereinafter), and carbon fluorides were generated when the potential fell into 6–8 V. In addition, some fluoride products could be reduced at about −0.22 V during reverse cyclic voltammetry scan, which has never been reported. Anode potential fluctuation was found between 6 and 8 V during galvanostatic electrolysis due to the formation of gaseous products as well as change of anode surface area and current density. Both Raman and X-ray photoelectron spectroscopy were employed to probe the chemical states of fluorination/oxidation products on graphite anode after electrolysis. The formation of fluorocarbon species is responsible for the disorder on graphite surface.